Long noncoding RNA NEAT1 modulates immune cell functions and is suppressed in early onset myocardial infarction patients - Gast, Martina; Haas, Jan; Meder, Benjamin (Cardiovascular research, 2019)
AbstractAims. Inflammation is a key driver of atherosclerosis and myocardial infarction (MI), and beyond proteins and microRNAs (miRs), long noncoding RNAs (ln
Gesehen am 10.01.2020
Online publish-ahead-of-print 29 March 2019